The effect of storage temperature and percentage of condensed distillers solubles on the shelf-life of distillers wet grains stored aerobically. (May 2015) - McClurkin, Janie D.; Ileleji, Klein E.
Abstract: Distillers wet grains with solubles (DWGS) are widely used as a supplemental protein source in North American cattle rations. However, due to its short shelf-life, its use is limited to feedlots within close proximity of an ethanol production plant. It is known that the shelf-life of DWGS in the summer diminishes drastically compared to in the winter. This effect is primarily due to temperature, which drives mold growth in high moisture feedstocks. The purpose of this study was to understand and quantify the effect of temperature (10, 20, and 25 °C) and condensed distillers solubles (CDS) levels [0%, 20% and 30%] on the shelf-life of DWGS under warm and cool aerobic storage conditions. Sample conditions which indicate shelf-life and product deterioration such as moisture content (m.c.), pH, fat acidity (FA), fungal growth and mycotoxin levels were measured in the DWGS samples before and after seven days of storage under three temperature levels (10, 20, and 25 °C). It was found that changes in temperature had the most significant effect on sample conditions (P < 0.05). After seven days of storage, m.c. and water activity (aw ) decreased with increase in temperature. In comparison, it was determined that FA, pH, fungal growth and mycotoxin levels increased with temperature after seven days of storage. Also, FA and CFU increased with increase in CDS level in DWGS. It was concluded that after seven days of storage at both warm and cool aerobic storage conditions, FA, aflatoxin, fumonisin and zearalenone levels increased. DWGS deteriorated less at 10 °C than at 20 °C and 25 °C, likewise less deterioration in 0% CDS than in 20% and 30% was noted. Highlights: Temperature had the greater effect on the parameters measured than CDS content. Of the parameters, which correlate to shelf-life, FA, pH and CFU values were sufficient in expressing spoilage. The study indicated that DWGS deteriorated less at 10 °C (cool weather) than at 20 or 25 °C (warm weather).